AWARENESS OF SOCIAL MEDIA BASIS AS A PROMOTIONAL MEDIUM FOR KULINTANGANTRADITIONAL MUSIC OF SUNGAI TRIBES AT PAITAN - Norezan, Jupin; Nor Atikah, Dolhan; Easther, Indang; Qistina Donna, Lee Abdullah (UNIMAS Publisher, 2021)
This article discussed the awareness level of Sungai Tribes on using social media as a promotional medium for Kulintangan traditionalmusic at Paitan. This study used a Quantitativeapproach through a survey of 377 people whoexpert in playing Kulintangan traditional musicand owned various social media (Facebook,YouTube, Instagram, and WhatsApp). Based on the fi ndings, the level of awareness of the Paitan cult on promoting Kulintangan via social media is moderate with a total average mean of 3.154 witha 1.302 standard deviation. The awareness of Sungai tribes on the usage of social media is more inclined to Whatsapp (ranking number 1 in overallmean and percentages) followed by Facebook,Instagram, and Youtube. Sungai tribes were also found to rarely share the Kulintangan music on social media account. Therefore, the SABAS and Sungai cult should increase the sharing of Kulintangan music via Whatsap